A first predictive mechanistic model of cold-water coral biomass and respiration based on physiology, hydrodynamics, and organic matter transport - de Froe, Evert; Mohn, Christian; Soetaert, Karline; van der Kaaden, Anna Selma; Reichart, Gert Jan; De Clippele, Laurence H.; Maier, Sandra R.; van Oevelen, Dick (Copernicus Publications, 2026)
Cold-water corals form complex three-dimensional structures on the seafloor, providing habitat for numerous species, and act as a carbon cycling hotspot in the deep-sea. The distribution of these important ecosystems is often predicted by statistical habitat suitability models, using variables such as terrain characteristics, temperature, salinity, and surface productivity. While useful, these models do not provide a mechanistic understanding of the processes that facilitate cold-water coral occurrence, and how this may change in the future. Here, we present the results of a mechanistic process-based model in which coral biomass and respiration are predicted based on hydrodynamics, organic matter transport and coral physiology. The model domain comprises the cold-water coral mounds of south-east Rockall Bank in the north-east Atlantic Ocean. Hydrodynamic forcing is provided by a high-resolution Regional Ocean Modelling System (ROMS) model, which drives the transport of reactive suspended particulate organic matter in the region. The physiological cold-water coral model, with coral food uptake, assimilation, and respiration as key variables and with model parameters estimated from available experimental reports, is coupled to the reactive transport model of suspended particulate organic matter. Cold-water coral biomass was mainly predicted on coral mounds and ridges in the area. Model predictions agree with coral reef biomass and respiration observations in the study area and coral occurrences agree with predictions from previously published habitat suitability models. Filter feeding activity by cold-water corals proved to strongly deplete food particles in the bottom waters. Replenishment of food particles by tidal currents was therefore vital for cold-water coral growth. This mechanistic modelling approach has the advantage over statistical and machine learning-based predictions that it can be used to obtain an understanding of the effect of changing environmental conditions such as ocean temperature, surface production export, or ocean currents on cold-water coral biomass distribution and can be applied to other study areas and/or species.
Keywords: Oceanography; Palaeontology